2018
DOI: 10.20524/aog.2018.0281
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotype 3: clinical features, current and emerging viral inhibitors, future challenges

Abstract: Hepatitis C virus (HCV) represents a global burden on healthcare that affects over 150 million people worldwide. In the past, HCV genotype 3 was considered difficult to treat relative to other genotypes. Genotype 3 has been associated with a higher rate of complications, including fatty liver disease, fibrosis, hepatocellular carcinoma and mortality. However, with the advent of first- and second-generation direct-acting antivirals, genotype 3 can be treated effectively. Additionally, these new drugs are well t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 109 publications
0
24
0
3
Order By: Relevance
“…Therefore, long term follow-up studies are required for determining hepatic brosis progression rates. A possible explanation for this nding may be that a high percentage of mono-infected individuals in this study were infected with HCV genotype 3a (51%) which is the strain most associated with rapid brosis progression (20)(21)(22). Our study also found higher BMIs and CAP scores in mono-infected individuals than in co-infected individuals, which may re ect a higher degree of liver steatosis leading to aggressive liver brosis progression (23).…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, long term follow-up studies are required for determining hepatic brosis progression rates. A possible explanation for this nding may be that a high percentage of mono-infected individuals in this study were infected with HCV genotype 3a (51%) which is the strain most associated with rapid brosis progression (20)(21)(22). Our study also found higher BMIs and CAP scores in mono-infected individuals than in co-infected individuals, which may re ect a higher degree of liver steatosis leading to aggressive liver brosis progression (23).…”
Section: Discussionmentioning
confidence: 48%
“…Contrary to this, globally, genotype 1 is estimated to be approximately 46.2%. HCV genotype 3 is the second most common type and makes up to 30.1% cases globally, approximately three-quarters of them are in [14] South Asia .…”
Section: Discussionmentioning
confidence: 99%
“…Globally, approximately 150 million people are living with HCV infections. [33] HCV is a single-stranded RNA virus of the Flaviviridae family with seven major genotypes (HCV1-7). [34] High-throughput antiviral drug discovery screens have been extensively performed to identify inhibitors of viral protease (serine protease for HCV) and inhibitors of the RNA-dependent RNA polymerase (RNA replicase).…”
Section: Denv Helicase Inhibitorsmentioning
confidence: 99%